Retroperitoneal involvement with light chain amyloidosis- case series and literature review. Issue 2 (28th January 2021) - Vaxman, Iuliana; Visram, Alissa; Pasvolsky, Oren; Kumar, Shaji; Dispenzieri, Angela; Buadi, Francis; Dingli, David; Lacy, Martha; Hayman, Suzanne; Kyle, Robert; Kapoor, Prashant; Leung, Nelson; et al.
Abstract: Retroperitoneal involvement is rare in patients with light chain (AL) amyloidosis and has only been published as case reports. Only 5 cases of retroperitoneal deposition have previously been reported in the setting of systemic AL amyloidosis. Data regarding the characteristics and clinical course of these patients are scarce. Herein we report on eleven patients with systemic AL amyloidosis diagnosed with retroperitoneal deposition at all three Mayo Clinic sites and Davidoff cancer center in Israel. All patients had retroperitoneal amyloid deposition at presentation. All patients received systemic treatment. Eight patients presented with hydronephrosis and 7 had nephrostomy tubes or stents inserted. Regression of the deposition was documented in one patient and one patient was able to have his nephrostomy tube removed. The median OS from diagnosis was 150 months, suggesting that retroperitoneal deposition might confer improved prognosis compared to the general amyloid population.